The educational evaluation in Brazil: from the transfer cultural to emancipatory evaluation - Adolfo Ignacio Calderón; Regilson Maciel Borges (Pontificia Universidad Católica del Perú, 2013)
This article discusses the historical trajectory of educational assessment in the Brazilian academic scenario, pointing out the influence of American literature on the Brazilian scientific production, its models break as well as the efforts in order to construct a theory and a practical assessment applied to the Brazilian reality. It supports the hypothesis that educational evaluation is still an area of knowledge that is in process of setting up and strengthening in the country, the last two decades enabled them to overcome the named «cultural transfer» in the field of scientific production, allowing the constitution and hegemony of an approach grounded on a emancipatory political-pedagogical character in the scientific community